(untitled) (Journal of Interdisciplinary Insights, 2025)
In the process of globalization and modernization, the construction of ethnic communities has become a core issue in the governance of multi-ethnic states. This paper, based on cultural identity theory, constructs an analytical framework of "historical memory, value consensus, and symbolic representation" to conduct a comparative study of the paths taken by China and typical European multi-ethnic states in building ethnic communities. The research finds that China has formed a path of cultural identity construction with "plural unity" at its core, characterized by state-led efforts through historical narrative integration, shaping of core values, and innovation in symbolic systems, achieving deep integration of ethnic and national identities. European countries, on the other hand, exhibit characteristics of "citizen integration and plural co-governance," relying on equal cultural rights within institutional frameworks and interactions in the public sphere, but face tensions between cultural pluralism and identity politics. The differences in historical foundations, driving mechanisms, and practical strategies between these two paths essentially reflect the interactive logic between civilizational traditions and modernity aspirations. The study proposes that the construction of ethnic communities in multi-ethnic states should balance cultural diversity and unity, building dynamic consensus in historical inheritance, providing new analytical perspectives for contemporary state governance.